Effect of glucomannan and potassium sorbate on quality and shelf life of fresh-cut cantaloupe - Morakot, Nuttawut; Vatanyoopaisarn, Savitri; Thumthanaruk, Benjawan; Wongsa, Jittimon; Puttanlek, Chureerat; Uttapap, Dudsadee; Lamsal, Buddhi P.; Rungsardthong, Vilai (Science, Engineering and Health Studies, 2020)
The objective of this research was to study the effects of glucomannan, and potassium sorbate on the quality and shelf-life of fresh-cut cantaloupes, which were stored at 6±2°C for 9 days. The concentrations of glucomannan studied were 0.05, 0.10, 0.15 and 0.20% (w/v). Results indicated that the coating solution containing 0.5% (w/v) of calcium chloride and 0.05% (w/v) glucomannan could help maintain weight loss, hardness and firmness, of the samples. However, the increase of glucomannan concentration to 0.10, 0.15, and 0.20% (w/v) showed adverse effects to most quality aspects of the fresh-cut samples. The microbial load of the coated cantaloupe at all concentrations of glucomannan was still high and could extend the shelf life of the samples to 1 day or less. Subsequently, the optimal concentration of potassium sorbate was investigated at 0.05, 0.10, and 0.15% (w/v). Results indicated that the coating solution containing 0.5% (w/v) of calcium chloride and 0.05% (w/v) glucomannan could inhibit the microbial growth, especially bacteria at all concentrations of potassium sorbate studied. Additionally, the coating mixture with potassium sorbate at 0.15% (w/v) could preserve the fresh-cut cantaloupes for a maximum of 5 days with safer microbial loads for commercial use.